Conceptualizing RRI from a Global South perspective through Indigenous innovation practices in Aotearoa New Zealand’s high-tech science sector - Maria Amoamo; Katharina Ruckstuhl (Journal of Responsible Innovation)
The dominance of a ‘North-Centric’ approach to RRI has made invisible a range of practices and stakeholders observed in the Global South that provide a multi-cultural perspective to aligning science with society. We use a practice theory lens and a three-part model of materials, competence, and meanings to examine RRI as a sci-tech management approach operating at the interface of western and Indigenous science. We present a case study of New Zealand’s high-tech science sector whereby local Indigenous (Māori) knowledge, expressed in a specific national policy called Vision Mātauranga (VM) is driving RRI in practice. The findings show a set of micro-practices, including open innovation, capacity development and absorptive capacity as necessary to initiate and sustain RRI collaborations with Māori. We conclude that a decolonized RRI process extends responsible innovation’s application beyond the EU, giving rise to the development and practice of new modes of science organizations and governance in RRI.